The Effect of Jigsaw Method on Fiqih Learning Outcomes in Madrasah Tsanawiyah - Ahmad Yenuri, Ali; Sholikah (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This study aims to find out whether there is an influence of the use of the jigsaw method on learning outcomes in students of fiqih class VIII MTs Sat Gresik and how much influence the jigsaw method has on learning outcomes in fiqih lesson students in Mts. Researchers used Pre Experimental with Design One Group Pretest-Postest. In this design, it only uses one group, namely the experimental group without a control group. The population is class VIII which numbers 13 students. Its data collection techniques use tests, and observations. The data analysis technique uses the T-test and KD formulas. The results showed that there was an influence of the jigsaw method in improving learning outcomes in students of Fiqh class VIII MTs lessons.